Characterization of BaFe12O19/Co3O4 using mechanical alloying approach for microwave absorbing materials - Martha Rianna; Graselita M.P. Lumban Batu; Adhere L.; Timbangen Sembiring; Muhammad Khalid Hussain; Akrajas Ali Umar; Nanang Sudrajat; Eko Arief Setiadi; Anggito Pringgo Tetuko; Perdamean Sebayang (Case Studies in Chemical and Environmental Engineering)
In this research, the BaFe12O19/Co3O4 material was carried out using the mechanical alloying approach with variations in Co3O4 composition of (10, 15, 20) wt%. The characterizations were using XRD, SEM-EDX, and VNA. The results of XRD analysis show that increasing crystal diameter increases Co3O4 compositions. SEM analysis results show that BaFe12O19 particles tend to form larger with the addition of Co3O4 particles, causing agglomeration. EDX shows that the percentage of Co3O4 increases, and the number of Fe atoms decreases while the number of Co atoms increases, indicating that Co ions replace Fe ions. The results of VNA analysis showed that the addition of 10 % Co3O4 composition had optimum absorption compared to other samples with a reflection loss of −22.7dB at a frequency of 10.88 GHz with an absorption percentage of 99.46 %.